Determinants of private sector credit in Uganda: the role of mobile money - Dorothy Nampewo; Grace Ainomugisha Tinyinondi; Duncan Roy Kawooya; George Wilson Ssonko (Financial Innovation, 2016)
Background: Mobile money services have been associated with unprecedented access to financial services, notably to under-banked and unbanked populations. Thus, mobile money opens a channel through which to examine the supply of private sector credit in Uganda. This study investigates how mobile money services influence private sector credit growth. Methods: We applied the vector error correction (VEC) model and Granger causality analysis to Ugandan data from March 2009 to February 2016, the period when mobile money services were introduced. Results: The VEC model reveals that mobile money has a significant positive long-run association with private sector credit growth. Granger causality analysis reveals long-run unidirectional causality from mobile money to private sector credit. Conclusions: Mobile money is critical for financial intermediation because it attracts resources from both the banked and the unbanked populations into the formal financial system, facilitating private sector credit growth.
Keywords: 650; Mobile money; Private sector credit; Uganda